ECONOMIC ANALYSIS TO THE ROLE OF THE PUBLIC AND PRIVATE SECTORS IN AGRICULTURAL DOMESTIC PRODUCT IN IRAQ - S. H. Nayyef,; A. F. Ahmed,; M. KH. Mohammed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The aim of the study is determining the effect of public and private also support and government loans in Agricultural domestic product by analyzing data that got it from secondary sources to the variables contained in the model during the period (1990-2020) using Autoregressive Distributed Lag model (ARDL) with software Eviews 10. The study finds that positive relationship between agriculture domestic product and explaining variables. We find significant parameters in the short and long run, explained that is the increase in agricultural loans with 1% lead to an increase in agricultural domestic product with 14%. Also, an increase in agricultural support with 1% lead to an increase in agricultural domestic product with 8%. Furthermore, an increase in private agricultural investment with 1% lead to increase in Agricultural domestic product with 3% and Increase in public agricultural investment with 1% lead to increase in Agricultural domestic product with 7% and that is refer to the importance role of public sector with the importance of private sector with agricultural policies as investment and financing policies as well as government support policy which works of expand production capacities and support the private sector  .the study is recommended to expansion the function of the Agricultural mutual Bank and to provide capital to producers by the agricultural initiative and to put a strategy to development and give an incentive the private sector.